2009
DOI: 10.1016/j.cbpb.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Robust cross-links in molluscan adhesive gels: Testing for contributions from hydrophobic and electrostatic interactions

Abstract: The cross-linking interactions that provide cohesive strength to molluscan adhesive gels were investigated. Metal-based interactions have been shown to play an important role in the glue of the slug Arion subfuscus (Draparnaud), but other types of interactions may also contribute to the glue's strength and their role has not been investigated. This study shows that treatments that normally disrupt hydrophobic or electrostatic interactions have little to no effect on the slug glue. High salt concentrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…When proteins were separated by gel filtration and spotted directly onto a membrane without denaturation, most did not stain for the presence of carbonyls, though there was some staining centered around the fractions containing asmp-40 [which eluted as a giant complex, as seen by Smith et al (Smith et al, 2009)] (Fig.2). There was no detectable staining in the fractions containing asmp-15, despite containing the largest amount of protein.…”
Section: Accessibility Of Carbonyl Groupsmentioning
confidence: 76%
See 2 more Smart Citations
“…When proteins were separated by gel filtration and spotted directly onto a membrane without denaturation, most did not stain for the presence of carbonyls, though there was some staining centered around the fractions containing asmp-40 [which eluted as a giant complex, as seen by Smith et al (Smith et al, 2009)] (Fig.2). There was no detectable staining in the fractions containing asmp-15, despite containing the largest amount of protein.…”
Section: Accessibility Of Carbonyl Groupsmentioning
confidence: 76%
“…In addition, there are likely to be significant amounts of other common divalent ions such as calcium and magnesium, which may also contribute to direct cross-links. Finally, asmp-40 forms large complexes that are insensitive to EDTA (Smith et al, 2009) and do not show a high level of oxidation. These may be cross-linked in a different way.…”
Section: The Role Of Oxidation In the Context Of Other Cross-linking mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this hypothesis, exposure to Cu 2+ was shown to represent a sublethal stressor in pleurocercid snails (Paulson et al, 1983) and was toxic for bivalves and polychaetes as well as gastropods (Kidwai and Ahmed, 1999;Cheung et al, 2002). Smith et al (2009) showed that metal chelation disrupts the crosslinking of macromolecule polymer gels in gastropod mollusks. These adhesive gels carry relatively high percentages of negatively charged amino acids (Pawlicki et al, 2004) that exhibit high-affinity EDTA-sensitive binding of divalent cations such as Ca 2+ and Mg 2+ (Smith et al, 2009) and should therefore be strongly affected by electrolytically produced protons and Cu 2+ .…”
Section: Discussionmentioning
confidence: 79%
“…Smith et al (2009) showed that metal chelation disrupts the crosslinking of macromolecule polymer gels in gastropod mollusks. These adhesive gels carry relatively high percentages of negatively charged amino acids (Pawlicki et al, 2004) that exhibit high-affinity EDTA-sensitive binding of divalent cations such as Ca 2+ and Mg 2+ (Smith et al, 2009) and should therefore be strongly affected by electrolytically produced protons and Cu 2+ . Accordingly, heavy metals such as Cu 2+ impact gastropod chemoreception, resulting in decreased feeding behavior, foot paralysis and death (Cuthbert et al, 1976).…”
Section: Discussionmentioning
confidence: 99%